Vestibular dysfunction is an important contributor to the aging of visuospatial ability in older adults–Data from a computerized test system - Zhang, Xuehao; Huang, Yan; Xia, Yuqi; Yang, Xiaotong; Zhang, Yanmei; Wei, Chaogang; Ying, Hang; Liu, Yuhe (Frontiers in Neurology, 2022)
Background A convergence of research supports a key role of the vestibular system in visuospatial ability. However, visuospatial ability may decline with age. This work aims to elucidate the important contribution of vestibular function to visuospatial ability in old adults through a computerized test system. Methods Patients with a clinical history of recurrent vertigo and at least failed one vestibular test were included in this cross-sectional study. Healthy controls of three age groups: older, middle-aged, and young adults were also involved. Visuospatial cognitive outcomes including spatial memory, spatial navigation, and mental rotation of all the groups were recorded. Comparing the performance of the visuospatial abilities between patients and age-matched controls as well as within the controls. Results A total of 158 individuals were enrolled. Results showed that patients performed worse than the age-matched controls, with the differences in the forward span (p < 0.001), the time of the maze 8 × 8 (p = 0.009), and the time of the maze 12 × 12 (p = 0.032) being significant. For the differences in visuospatial cognitive outcomes within the controls, the younger group had a significantly better performance than the other groups. The older group and the middle-aged group had comparable performances during all the tests. Conclusions Older patients with vestibular dysfunction had more difficulties during visuospatial tasks than age-matched controls, especially in spatial memory and spatial navigation. Within the controls, younger adults did much better than other age groups, while older adults behaved similarly to middle-aged adults. It is a valuable attempt to computerize the administration of tests for visuospatial ability.